Barreiras residuais ao direito educacional em cursos integrados do Instituto Federal do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This thesis aimed to investigate the residual barriers to the educational right of students belonging to the groups contemplated by the Quotas Law (Law n. 12.711/2012a) in the integrated technical courses of the Federal Institute of Paraná (IFPR). IFPR is one of 38 Federal Institutes of Education, Science, and Technology (IFs) in Brazil, which offer technical, higher, and graduate-level education 100% free of charge, and encourage upward advancement in schooling in a path known as verticalization. According to Law 11.892/2008, the IFs' technical courses integrated to high school are aimed at promoting integral education, both for professionalization and for life, which expands the possibilities of generating employment and income and attracts subjects from various social classes, due to the qualitative recognition that federal institutions have in Brazilian society. In order to democratize the access of students who, historically, have fewer educational opportunities, the Law 12.711/2012 establishes a minimum percentage of 50% of vacancies reserved for students coming from public schools, with percentage subdivisions according to income, race/color, and/or disability criteria. The IFPR goes beyond the established and, since 2014, allocates 80% of the total in all classes to the priority vacancies reservation system, however, only in 2020 the vacancies reserved for quotas were occupied in their entirety in integrated technical courses. This is a qualitative and quantitative study that uses bibliographic and documentary research methods, interviews, semistructured questionnaires, and focus groups. The study was carried out in eight of the twenty-seven cities in the state of Paraná that have an IFPR unit (Foz do Iguaçu, Irati, Ivaiporã, Jacarezinho, Palmas, Paranaguá, Telêmaco Borba, and Umuarama), selected by criteria classification (campus), length of activity (more than five years), geographical distribution and socioeconomic indicators of the city where the campus is located: percentage of the population with nominal monthly per capita income below 1⁄2 minimum wage; Gini Index and Firjan Development Index (the latter for contemplating the same variables of the human development index, however, being more updated). The results of the field research were obtained from an analysis corpus of 39 subjects, being eight directors of IFPR campuses, eighteen directors of state schools and thirteen students who entered through quotas in integrated technical courses. These allowed us to identify the existence of residual barriers to the educational right to integrated courses at IFPR, which we propose to list in four categories: I) institutional barriers; II) territorial and displacement barriers; III) socioeconomic barriers and IV) invisible/symbolic barriers. The discussion of the results contemplated the contradictions and intersections between the barriers identified.
Keywords: barreiras residuais; reservas de vagas; Instituto Federal do Paraná (IFPR); ensino médio integrado; educação integral; residual barriers; vacancy reserves; Federal Institute of Paraná (IFPR); integrated high school; integral education; CNPQ::CIENCIAS SOCIAIS APLICADAS